Deteksi Keberadaan Mikroba Indikator Dalam Es Kelapa Muda (Cocos Nucifera) Di Kecamatan Ujung Batu Kabupaten Rokan Hulu - Rio Andri; Al Muzafri; Lufita Nur Alfiah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Coconut ice is a food product that is considered safe for consumption, young coconut ice is made from young coconut mixed with ice crystals and served in the form of a drink. Even though it is served in a clean place to avoid the presence of microorganisms, young coconut ice still has the possibility of microorganisms containing microbial contamination. This study aims to detect the presence of Coliform in young coconut ice (Cocos nucifera), from various drinks sold in Ujung Batu District, Rokan Hulu Regency. The research method used is Random Sampling, has been carried out from September to November 2021. The MPN (Most Probable Number) method is used to calculate Coliform. A total of 8 samples were used in this study. Observations showed that all positive samples contained Coliform. Factors that can be a source of contamination such as ice crystals, young coconuts, tools and hygiene practices by sellers need to be considered so that young coconut water ice is free from Coliform contamination. The population of this research is young coconut ice, covering Ujung Batu Subdistrict in Pematang Tebih Village, Suka Damai Village, Ujung Batu Village and Ngaso Village. The sampling technique was random sampling based on the amount of coconut ice purchased from traders. The results of data analysis showed that young coconut ice had been contaminated by coliform bacteria. Laboratory examination 8 samples contained coliform microbes, 6 samples (>1600), 1 sample (1600) and 1 sample (150) of the total samples. According to the Minister of Health of the Republic of Indonesia No.492/MENKES/PER/IV/2020 concerning the requirements for drinking water quality, it is stated that the number of coliform bacteria and Escherichia coli bacteria in drinking water is 0/100 ml of water sample.